Poetics of the Intruder. Jacques Rancière’s Mallarmé - Bejarano, Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This essay analyzes the meaning of the figure of the poet as intruder in Stéphane Mallarmé’s works, as it is studied by the French critical theorist and philosopher Jacques Rancière in Politics of the Siren and Mute speech . Our intention is to reflect about and expand definitions of the role of the poet and the literary space in one of the most remarkable creators of contemporary art.